2003
DOI: 10.1038/sj.jea.7500290
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of exposure to a flood disaster in a mental-health study

Abstract: The lasting psychological consequences of disasters are an important public health issue, especially for determining the support needed by victims. One important question in evaluating psychological consequences remains the assessment of individual disaster-related experiences or stressors. This article proposes two approaches towards the construction of cumulative exposure indicators (CEIs) for a disaster and discusses their relevance for other disasters. In 1997, we carried out a cross-sectional study of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 27 publications
3
40
0
Order By: Relevance
“…These accounts may be affected by the shocking experience and the impacts suffered and may therefore be not entirely reliable. However, literature suggests that a good recall of disaster experiences is actually possible, even over long periods of time (Baum et al 1983, Verger et al 2003. In our study, the consistence of results with other biophysical reports and the congruence between the magnitude of transformations and the impacts on levels of well-being in different geographical sectors, suggests the validity of respondents' recall.…”
Section: Discussionsupporting
confidence: 57%
“…These accounts may be affected by the shocking experience and the impacts suffered and may therefore be not entirely reliable. However, literature suggests that a good recall of disaster experiences is actually possible, even over long periods of time (Baum et al 1983, Verger et al 2003. In our study, the consistence of results with other biophysical reports and the congruence between the magnitude of transformations and the impacts on levels of well-being in different geographical sectors, suggests the validity of respondents' recall.…”
Section: Discussionsupporting
confidence: 57%
“…[1][2][3][4][5] The most severe involve flash flooding and landslides and are most commonly associated with post-traumatic stress disorder in survivors. 6 The psychological impact of these types of floods is comparable to that of earthquakes, volcanoes and tsunamis. 1,2,5-7 The type of flooding that affected…”
Section: Discussionmentioning
confidence: 88%
“…Operational briefs are important to identify areas for improvement and lessons learned but do not generally capture the public's perspective (Pfister 2002). Lasting psychological consequences associated with disaster events are another public health issue in determining victim support (Verger et al 2003). Research in the US has found that in disasters communities rely on assistance from many authorities and organisations Gazley et al 2009;McGuire et al 2009) and there is a growing realization that, with the exception of smaller emergencies, no one organisation is capable of doing it all ).…”
Section: Lessons Learned From Previous Flood Studiesmentioning
confidence: 99%